Physiological tolerance to uncompensated heat stress in soldiers: effects of various types of body cooling systems - Jovanović, Dalibor; Karkalic, Radovan; Zeba, Snježana; Pavlović, Miroslav; Radaković, Sonja S. (Vojnosanitetski pregled, 2014)
Background/Aim. In military services, emergency situations when soldiers are exposed to a combination of nuclear, biological and chemical (NBC) contamination combined with heat stress, are frequent and complex. In these specific conditions, usage of personal body cooling systems may be effective in reducing heat stress. The present study was conducted in order to evaluate the efficiency of four various types of contemporary personal body cooling systems based on the “Phase Change Material” (PCM), and its effects on soldiers’ subjective comfort and physiological performance during exertional heat stress in hot environments. Methods. Ten male soldiers were voluntarily subjected to exertional heat stress tests (EHSTs) consisted of walking on a treadmill (5.5 km/h) in hot conditions (40ºC) in climatic chamber, wearing NBC isolating impermeable protective suits. One of the tests was performed without any additional cooling solution (NOCOOL), and four tests were performed while using different types of cooling systems: three in a form of vests and one as underwear. Physiological strain was determined by the mean skin temperature (Tsk), tympanic temperature (Tty), and heart rate values (HR), while sweat rates (SwR) indicated changes in hydration status. Results. In all the cases EHST induced physiological response manifested through increasing Tty, HR and SwR. Compared to NOCOOL tests, when using cooling vests, Tty and Tsk were significantly lower (on 35th min, for 0.44 ± 0.03 and 0.49 ± 0.05ºC, respectively; p < 0.05), as well as the average SwR (0.17 ± 0.03 L/m2/h). When using underwear, the values of given parameters were not significantly different compared to NOCOOL tests. Conclusions. Using a body cooling system based on PCM in the form of vest under NBC protective clothes during physical activity in hot conditions, reduces sweating and alleviates heat stress manifested by increased core and skin temperatures and heart rate values. These effects directly improve heat tolerance, hydration state, decrease in the risk of heat illness, and extends the duration of soldiers’ exposure to extreme conditions.